IMPLEMENTATION OF EXPERIENTAL LEARNING MODELS TO IMPROVE REASONING ABILITY OF STUDENT’S SMP - Antik Vinayanti; Fika Muji Fadhillah (IKIP Siliwangi, 2019)
Experimental learning invites students to play an active role during the learning process based on life experiences that can be applied into four stages, namely concrete experience, observation, conceptualization and application. conventional, 2) knowing the improvement of mathematical reasoning abilities of students who get learning using the experiential learning method better than conventional learning. The method used in this study is the experimental method by taking a sample of this study is the seventh grade students of SMP Negeri 2 Klangenan in Cirebon Regency. Implementation data with an experimental learning model was obtained through observation sheets and students' mathematical reasoning abilities were obtained through description tests. The results of the study for four meetings showed that there was an increase in the average results of the pretest and posttest. From the results of statistical tests of gain scores obtained from the results of the pretest and posttest on students' mathematical reasoning abilities the average (ẋ) gain for the experimental class is 0.64 with a standard deviation (s) = 0.6 based on these results. that students' mathematical reasoning abilities using experiential learning are better than students who are conventional learning.